2009
DOI: 10.1016/j.bbmt.2009.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Receiving Information on Fertility- and Menopause-Related Treatment Effects among Women Who Undergo Hematopoietic Stem Cell Transplantation: Changes in Perceived Importance Over Time

Abstract: Hematopoietic stem-cell transplantation (HSCT) is associated with high rates of gonadal failure, which is distressing for younger patients desiring to start a family. The perceived importance and optimal timing of discussing fertility- and menopause-related information with women undergoing aggressive treatment such as HSCT is not well defined. Questionnaires were sent to 532 patients who underwent HSCT between January 1987 and September 2004 at the ages of 16 to 50 years. The questionnaire assessed demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 29 publications
6
57
1
2
Order By: Relevance
“…Nine studies reported a mean or median age at cancer diagnosis, of which five had a study population diagnosed at the age of 35 years or older (Armuand et al, 2012;Mancini et al, 2008;Penrose et al, 2012;Thewes et al, 2003Thewes et al, , 2005. Twelve studies documented the average age at study participation, of which four reported a study population of 40 years and over (Armuand et al, 2012;Karaö z et al, 2010;Mancini et al, 2008;Nakayama et al, 2009). Half of the studies included patients with different types of cancer (Anderson et al, 2008;Armuand et al, 2012;Chapple et al, 2007;Crawshaw et al, 2009;Huyghe et al, 2009;Mancini et al, 2008;Penrose et al, 2012;Tschudin et al, 2010;Wilkes et al, 2010;Zebrack, 2008Zebrack, , 2009.…”
Section: Results Of Studies Focusing On Patient Perspectivementioning
confidence: 95%
See 1 more Smart Citation
“…Nine studies reported a mean or median age at cancer diagnosis, of which five had a study population diagnosed at the age of 35 years or older (Armuand et al, 2012;Mancini et al, 2008;Penrose et al, 2012;Thewes et al, 2003Thewes et al, , 2005. Twelve studies documented the average age at study participation, of which four reported a study population of 40 years and over (Armuand et al, 2012;Karaö z et al, 2010;Mancini et al, 2008;Nakayama et al, 2009). Half of the studies included patients with different types of cancer (Anderson et al, 2008;Armuand et al, 2012;Chapple et al, 2007;Crawshaw et al, 2009;Huyghe et al, 2009;Mancini et al, 2008;Penrose et al, 2012;Tschudin et al, 2010;Wilkes et al, 2010;Zebrack, 2008Zebrack, , 2009.…”
Section: Results Of Studies Focusing On Patient Perspectivementioning
confidence: 95%
“…One researcher (JG) extracted patient's individual demographics and performed basic statistical analyses by use of Excel. The following data were calculated: mean age and time since diagnosis (Wilkes et al, 2010), number of (post) pubertal girls informed about fertility (Anderson et al, 2008), and percentage of patients with a pre-treatment desire to have children (Nakayama et al, 2009).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Quality of life after cancer has thus become a major issue. Nakayama et al [38] conducted a survey study and reported that most patients believe that a discussion of fertility-related or menopausal-related issues was as important as a discussion of their cancer issues. The ASCO guideline recommends the discussion of ovarian preservation as early as possible in treatment planning [4].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the regimens used for allogeneic stem cell conditioning cause the most severe damage, especially in the case of total body irradiation (TBI), with POF and infertility almost constantly occurring in adults and in up to 81% of cases in children. 29,30 Pregnancies have been reported after conditioning with BEAM (carmustine, etoposide, cytarabine, melphalan) and autologous transplantation. A recent report from the Late Effects Working Committee of the Center for International Blood and Marrow Transplant Research (CIBMTR) concluded that some patients who received TBI and/or myeloablative conditioning can preserve their fertility.…”
Section: Treatments Of Refractory Lymphoma or Relapses And Second-linmentioning
confidence: 99%